'Crossing the bridge': land education teacher professional development. Issue 2 (27th May 2021) - Calderon, Dolores; Lees, Anna; Swan Waite, Renée; Wilson, Cynthia
ABSTRACT: We propose that the Indigenizing framework of land education in teacher professional development offers an opportunity to engage the epistemological constraints of white settler teachers. Building off the work of teacher education researchers who examine settler epistemic formations in teachers and document the gaps between euroamerican epistemic understandings of place and Indigenous understandings of place we identify axiological innovations in program design that help unsettle teachers' sense of place towards an indigenized framework of relationality. We draw from pre and post survey data collected from teachers that participated in a land education teacher professional development (LETPD) workshop conducted in partnership with a local tribal nation. We identify how settler epistemic positions are expressed, the epistemic gaps produced by settler teachers that prevent them from accessing the full scope of LETPD, and document teacher resistance to relational PD as well as beginning efforts toward transformation. Finally, we propose that future LETPDs work towards encouraging epistemic responsibilities that require deep observation, a disinvestment in western science as the single mode of knowledge, valuing non-western expertise, and a shift from nature as external to being in relation to.